Pengaruh Ekstrak Bunga Rosella (Hibiscus sabdariffa L.) Terhadap Kadar Glukosa Darah Pada Tikus Putih (Rattus norvegicus L.) Yang Diinduksi Aloksan - Faradila, Ratna; Ramadhan, Achmad; Sutrisnawati, Sutrisnawati; Isnainar, Isnainar; Dhafir, Fatmah; Budiarsa, I Made (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the effect of rosella flower extract on reducing blood glucose levels in alloxan-induced white rats. The research method used is an experiment conducted in the laboratory with a complete randomized design (RAL) pattern. The number of samples used was 24 white rats consisting of 6 treatment groups and 4 replicates. Normal control group (Kn) is a group that is only given food and drink, negative control group      (K-) is a group given alloxan induction, positive control group (K+) is a group given alloxan induction and metformin synthesized drug, treatment groups I, II, and III are groups given alloxan induction and rosella flower extract at a dose of 50 mg/kg BB, 100 mg/kg BB and 150 mg/kg BB. The data obtained were analyzed by ANOVA statistical test. The results showed that rosella flower extract had an effect on reducing blood glucose levels in white rats induced by alloxan. The most effective dose in reducing blood glucose levels in white rats is a dose of 150 mg/kg.